In situ diffraction studies of iron ore sinter bonding phase formation: QPA considerations and pushing the limits of laboratory data collection. Issue 1 (17th November 2014) - Webster, Nathan A. S.; Pownceby, Mark I.; Madsen, Ian C.; Studer, Andrew J.; Kimpton, Justin A.
<x content-type="archive" xml:space="preserve">Abstract</x> The formation and decomposition of silico-ferrite of calcium and aluminium (SFCA) and SFCA-I iron ore sinter bonding phases have been investigated using in situ synchrotron and laboratory X-ray diffraction (XRD) and neutron diffraction (ND). An external standard approach for determining absolute phase concentrations via Rietveld refinement-based quantitative phase analysis is discussed. The complementarity of in situ XRD and ND in characterising sinter phase formation and decomposition is also shown, with the volume diffraction afforded by the neutron technique reducing errors in the quantification of magnetite above ~1200 °C. Finally, by collecting 6 s laboratory XRD datasets and using a heating rate of 175 °C min−1, phase formation and decomposition have been monitored under heating rates more closely approximating those encountered in industrial iron ore sintering.